On The Study of Development of X Band Metamaterial Radar Absorber - M. A. Abdalla (Advanced Electromagnetics, 2012)
A new development of metamaterial applications in radar absorbers for X band is introduced. Two modifications were suggested based on two different approaches which are a new called fan shaped resonator absorber and a modified high impedance metamaterial absorber. Both approaches introduce thin radar absorber (5.3% at centre frequency) with wide bandwidth and high absorption level. The theoretical concepts of each design are explained and validated using full wave simulation. Results illustrate that the new development can achieve wider bandwidth, multiple operating bands; the increase in bandwidth is up to 8 times the conventional one. Moreover, the reported absorbers have capability to operate with different polarizations.